The toby man - King-Smith, Dick.; Hemmant, Lynette (New York : Crown, 1991)
Tod Golightly, a young highwayman, finds his fortune with the help of four loyal animal friends.
6.9
3-6
3-6
School Library Journal
Publisher's Weekly
Booklist
Keywords: Animals -- Fiction; Robbers and outlaws -- Fiction; Adventure and adventurers -- Fiction; Animals -- Fiction; Adventure and adventurers -- Fiction